PERANCANGAN SISTEM DETEKSI DINI SEL ABNORMAL RONGGA MULUT DENGAN METODE FLUORESCENCE VISUALIZATION DILENGKAPI STERILISASI OZONE PLASMA - Mochammad Rofi Sanjaya; n/a Nurussa’adah; Thareq Barasabha (Jurnal Mahasiswa TEUB, 2023)
The prevalence of oral cancer reached 14,197 cases from 2015 to 2020 in Indonesia. On the other hand, delay in cancer treatment can be fatal. However, there are less than 5 specialist dentists in some provinces, and even zero in West Papua. Therefore, screening by Public Health Center nurse needed to reduce oral cancer mortality rate. This scientific article aims to design, create, and test an early detection system for oral cancer based on IoT-integrated fluorescence imaging that is practical, functional, and clinically innovative. The method started in literature study, system design, fabrication, operational and clinical testing, and evaluation. System’s function examination is done by measuring HPL LED temperature, object temperature, and ozone plasmatemperature. A clinical trial was conducted on six subjects with linea alba, RAS, mucocele, ameloblastoma, leukoplakia, and behcet syndrome. Functional test resulted in the system components remains in 28,4˚C, the illuminated object temperature does not over 24,8˚C within 10 minutes, thus there is no heat side effects damaging components and things, and also the ozone temperature does not over 29,5˚C within 10 minutes. Clinical tests obtained 100% true negative results in all subjects. The oral cancer early detection system has been successfully made and tested. Functional tests show that the system has good durability, and clinical tests show true negatives in normal mucosa and non-malignant lesions. Keywords: teledentistry, screening, oral cancer, fluorescence visualization, ozone plasma DAFTAR PUSTAKA[1] S. D’souza and V. Addepalli, “Preventive measures in oral cancer: An overview,” Biomed. Pharmacother., vol. 107, no. May,pp. 72–80, 2018, doi: 10.1016/j.biopha.2018.07.114.[2] Kemenkes RI, “Data Tenaga Medis yang didayagunakan di Fasilitas Pelayanan Kesehatan (Fasyankes) di Indonesia,”bppsdmk, 2020. http://bppsdmk.kemkes.go.id/info_sdmk/info/index?rumpun=101 (accessed Feb. 13, 2022).[3] T. Morikawa et al., “Countermeasure and opportunistic screening systems for oral cancer,” Oral Oncol., vol. 112, no. March2020, p. 105047, 2021, doi: 10.1016/j.oraloncology.2020.105047.[4] N. Yamamoto et al., “Detection accuracy for epithelial dysplasia using an objective autofluorescence visualization method based on the luminance ratio,” Int. J. Oral Sci., vol. 9, no. 11, pp. 1–10, 2017, doi: 10.1038/ijos.2017.37.[5] M. Mascitti et al., “An overview on current non-invasive diagnostic devices in oral oncology,” Front. Physiol., vol. 9, no. OCT,pp. 1–8, 2018, doi: 10.3389/fphys.2018.01510.[6] A. Niveditha, R. Pandiselvam, V. A. Prasath, S. K. Singh, K. Gul, and A. Kothakota, “Application of cold plasma and ozonetechnology for decontamination of Escherichia coli in foods- a review,” Food Control, vol. 130, no. June, p. 108338, 2021,doi: 10.1016/j.foodcont.2021.108338.[7] M. Cicciù et al., “Early diagnosis on oral and potentially oral malignant lesions: A systematic review on the Velscope® fluorescence method,” Dent. J., vol. 7, no. 3, 2019, doi: 10.3390/dj7030093. [8] V. Taran et al., “Portable ozone sterilization device with mechanical and ultrasonic cleaning units for dentistry,” Rev. Sci. Instrum., vol. 91, no. 8, 2020, doi: 10.1063/1.5145279.[9] Ozone Solutions, “Ozone Effects on Bacteria, Viruses and Molds,” Ozone Solutions, 2021. https://ozonesolutions.com/blog/ozoneeffects-on-pathogens/ (accessed Oct. 20, 2022).[10] H. A. Adil, M. Yuwanati, A. Singh, S. Sawant, and H. R. Umarji, “Comparative study on the efficacy of Tissue Autofluorescence (Visually Enhanced Lesion Scope) and Toluidine Blue as a screening method in oral potentially malignant and malignant lesions,” J. Med. Sci., vol. 37, no. 3, pp. 91–96, 2017, doi: 10.4103/jmedsci.jmedsci_53_16.